Environmental Nihilism in the Age of Climate Deadlines - Mensah, Cocou Marius (65 pravne znanosti v Mariboru, 2026)
The urgency to confront environmental degradation has become a defining trait of our contemporary era. In the age of accelerating climate change, the persistence of widespread societal indifference and denial raises a troubling question: is our generation conscious of the climate emergency unfolding before us? This chapter confronts that attitude, described as environmental nihilism, with compelling scientific evidence warning of the risk of global ecological collapse. The discussion is framed by the milestones marking 50 years of the University of Maribor and 65 years of legal studies in Maribor, underscoring the responsibility of legal scholarship to engage with global challenges. It is argued that law, as both a normative framework and a practical governance instrument, must respond to the existential threat of climate change through robust international cooperation. By analysing landmark legal instruments, this article examines how law can counter societal nihilism and contribute to the achievement of climate-related goals.